2007
DOI: 10.1007/s10750-006-0533-1
|View full text |Cite
|
Sign up to set email alerts
|

Organization patterns of headwater-stream fish communities in the Upper Paraguay–Paraná basins

Abstract: We compared environmental influences on the assemblages of stream fishes of contiguous but biogeographically distinct parts of the Upper Paraguay and Paraná basins in Brazil, aiming to describe the main distribution patterns of fish species in the headwater streams. We analyzed bimonthly samples in 10 streams in each basin from January to November 2004. Sixty fish species were collected, including 40 species in streams of the Paraguay Basin and 42 species in streams of the Paraná Basin. The species abundance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
1
25
0
7
Order By: Relevance
“…Factors that influence the spatial distribution of fish species in streams (e.g., altitude, volume, flow and stream width: Oberdorff et al, 2001;Valério et al, 2007;Tondato and Súarez, 2010;Súarez et al, 2011) are different from those observed in floodplain ponds (Suarez et al, 2001(Suarez et al, , 2004. The composition of fish assemblages in temporary ponds of floodplains depends on multiple interactions with the environment: the occurrence of fish is uncommon during the isolation period because of drying out and limiting conditions (Baber et al, 2002) such as predation and competition for space (Okada et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Factors that influence the spatial distribution of fish species in streams (e.g., altitude, volume, flow and stream width: Oberdorff et al, 2001;Valério et al, 2007;Tondato and Súarez, 2010;Súarez et al, 2011) are different from those observed in floodplain ponds (Suarez et al, 2001(Suarez et al, , 2004. The composition of fish assemblages in temporary ponds of floodplains depends on multiple interactions with the environment: the occurrence of fish is uncommon during the isolation period because of drying out and limiting conditions (Baber et al, 2002) such as predation and competition for space (Okada et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…In recent decades, several studies of the spatial organisation of fish assemblages have shown that ecological patterns vary depending on space (Jackson et al, 2001;Tejerina-Garro and Mérona, 2001;Valério et al, 2007;Súarez et al, 2011). This spatial variation can be determined by environmental characteristics and interactions among species, as advocated by the niche theory (Hutchinson, 1957;Chase and Leibold, 2003), or by stochastic processes through random combinations of colonisation, as assumed by the neutral theory (Hubbell, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One consequence of this process would be the high rate of allopatric speciation (Castro, 1999). This idea is supported by the high number of undescribed species or in undefined taxonomic situation (Castro et al, 2003;Buckup et al, 2007;Langeani et al, 2007;Valério et al, 2007;Aquino et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rainfall influence on the migratory cycles targeted to feeding sites, and specially to reproductive activities in fish assemblages (Agostinho, 2004), the low seasonal influence on headwater streams ichthyofauna has been observed in upper Paraná basin studies, where spatial variation are more relevant to species distribution than seasonal variations, at least for most species (Langeani et al, 2005;Valério et al, 2007;Aquino, 2008;Súarez, 2008;Súarez & LimaJúnior, 2009). The low seasonal variation in fish assemblages of headwaters can be related to the higher stability (i.e., tendency to reduce fluctuations in the energy flow) in these systems when compared to high order streams.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be a pattern for all low-order streams of the Neotropical region (e.g., Vilella 2002, Langeani et al 2005, Valério et al 2007, Súarez 2008, Súarez & LimaJúnior 2009) because the temporal variation is mainly associated with the fish migration from the lower portions of the basin (Grossman & Ratajczak Junior 1998) and, as these streams present a small temporal variation of their hydrological characteristics (Súarez & Petrere Junior 2005) and also a higher stability than the higher order segments, with an almost constant energy flow throughout the year (Dudgeon 2008), they act as a "filter of species" (Poff 1997), preventing the colonization of migratory species in these environments.…”
Section: Discussionmentioning
confidence: 90%